Transparency of Hajj Fund Accountability: Performance of Financial Statements and Investment Optimization - Roymon Panjaitan; Echan Adam (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2022)
This research aims to provide a theoretical framework for implementing financial products in the management of Hajj financial funds presented in a transparent and accountable manner with a novelty system that is centrally embedded in the field. This research contribution integrates the management of centralised system fund instruments that are transparent and accountable. This research method uses sampling in the form of interview instruments and questionnaires to 126 employees who work in religious affairs offices located in branch offices on the island of Java. As a result of this research, there is a significant positive effect of direct or indirect integrated systems centralised on transparency and public accountability in producing good financial statement performance, and financial statement performance relationships have a significant positive effect on the optimisation of financial instruments